Solvent Co‐Intercalation‐Induced Activation and Capacity Fade Mechanism of Few‐/Multi‐Layered MXenes in Lithium Ion Batteries. Issue 47 (11th October 2021) - Bärmann, Peer; Winter, Martin; Gonzalez‐Julian, Jesus; Placke, Tobias
Abstract: MXenes attract tremendous research efforts since their discovery in 2011 due to their unique physical and chemical properties, allowing for application in various fields. One of them is electrochemical energy storage due to their pseudocapacitive (=redox) behavior, high electronic conductivity, and charge storage versatility regarding the cationic species (e.g., Li + ). MXenes typically display stable charge/discharge cycling behavior over hundreds of cycles in numerous electrolytes, however, a drastic loss of reversible capacity is detectable during the initial cycles. Furthermore, an electrochemical "activation" is also reported in the literature, especially for free‐standing electrodes. Here, these electrochemical phenomena are investigated by electrochemical and analytical means to decipher the responsible mechanism by comparing few‐layered and multi‐layered Ti3 C2 T x . A change in the pseudocapacitive behavior of MXenes during cycling can be explained by in situ X‐ray diffraction studies, revealing solvent co‐intercalation in the first cycle for the morphologically different MXenes. This co‐intercalation is responsible for the capacity decay detected in the first cycles and is also responsible for the ongoing "activation" occurring in later cycles. Abstract : Although MXenes manifest themselves as one of the most widely applied 2D material classes of the last century, many occurring fundamental electrochemical phenomena are still unexplained. One of which is the literature‐known capacity fading during formation followed by an "activation" with continuous cycling. This phenomenon is deciphered with the help of electrochemical (EIS) and analytical (in situ XRD) methods.